The real business of IT : how CIOs create and communicate business value - Hunter, Richard , 1952-; Westerman, George , 1963- (Gartner, Inc/Harvard Business School Press series, 2009)
The authors reveal that the cost mind-set, a real handicap to any business today, stems from IT leaders' inability to communicate about the business value they create, so CIOs get stuck discussing budgets rather than their contributions to the organization. Learn how to communicate effectively about value from IT investments